Globalisasi Budaya Musik Dangdut Koplo Melalui Media Tiktok (Pendekatan Komunikasi Lintas Budaya) - Kiram, Saiful (Lisyabab : Jurnal Studi Islam dan Sosial, 2023)
Dangdut music is no longer a local and ancient culture but has become a global or international culture. This is because dangdut music has now become one of the popular cultures in the current millennial era and has been introduced to foreign countries by Indonesian youths. Music sociologist Prof. Andrew N. Weintarub also added that dangdut music is an original culture from Indonesia, not from other countries and has been found in various regions and has been well received by all groups as well as being a unifier. This study aims to describe and analyze the phenomenon of Dangdut Koplo Music Culture on Tiktok Media, especially in the account posts belonging to the boyband "NCT Dream" which contain Mendungdut Tanpo Udan dancing and accompanied by background music from the band "Ndarboy Genk" in the view of cross-cultural communication. The results of this study are that in this phenomenon there has been a process of cross-cultural communication, there are also characteristics of cultural globalization from David Held's theory, namely the expansion of social relations (Stretched Social Relations) and increased intensity of communication (Intensification of Flows), and there is a theory Culture from EB Taylor where "NCT Dream" has gained knowledge, artistry, and skills in dangdut koplo music culture, especially dancing and the song "Mendung Tanpo Udan" from various media, especially from the TikTok account "Ndarboy Genk" so that they become part of Indonesian society.